Tissue Protective and Anti-Fibrotic Actions of Suramin: New Uses of an Old Drug - Liu, Na; Zhuang, Shougang (Current Clinical Pharmacology, 2011)
Suramin is a polysulfonated naphthylurea, which was originally synthesized and designed as a treatment for trypanosomiasis and selected malignancies and metastatic diseases. Increasing evidence indicates that suramin is also effective in interfering with many other pathophysiological processes in animal models. For example, suramin can enhance renal regeneration after ischemia/reperfusion injury, attenuate liver damage following CD95 stimulation and endotoxic shock, reduce brain injury induced by ischemia, and suppress myocardial inflammation. Further, suramin has an anti-fibrotic effect in liver and muscle. Mechanistic studies show that suramin inhibits apoptosis, suppresses expression of proinflammatory cytokines, inactivates myofibroblasts and stimulates proliferation of renal epithelial cells. This review highlights the novel actions of suramin in a variety of tissues and organs.
Keywords: myofibroblast